ANALISIS PENGGUNAAN DEIKSIS DALAM CERPEN BAHASA INDONESIA - Ach Zubairi; Ach Basri; Ach Zainuddin; Mas’odi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This study aims to analyze the use of deixis in Indonesian short stories, focusing on how these linguistic elements contribute to shaping the readers' perception of characters, setting, and plot. Deixis, as a part of pragmatic studies, refers to words or phrases whose meanings depend on the context of use, such as "I," "here," and "yesterday." Using a qualitative text analysis method grounded in pragmatics, this research identifies various types of deixis (personal, temporal, spatial, and social) in short stories and examines their impact on narrative interaction and the readers' experience. The findings reveal that personal and temporal deixis are the most dominant in the short stories analyzed. Personal deixis such as "I" or "you" fosters emotional closeness between the reader and the character, while temporal deixis helps organize the sequence of events and clarifies the plot. Additionally, spatial and social deixis enrich the understanding of the setting and the relationships between characters. In conclusion, the use of deixis in short stories not only aids readers in understanding the context of the narrative but also creates emotional bonds and specific perspectives. This research contributes to pragmatic studies and the analysis of Indonesian literature, particularly in understanding the role of language in shaping narrative and aesthetic experiences for readers